Can we accredit hospital ethics? A tentative proposal. Issue 8 (2nd June 2011) - Wu, Min-Hua; Liao, Chih-Hsien; Chiu, Wen-Ta; Lin, Ching-Ying; Yang, Che-Ming
Abstract : Objectives: The objective of this research was to develop ethics accreditation standards for hospitals. Research design: Our research methods included a literature review, an expert focus group, the Delphi technique and a hospital survey. The entire process was separated into two stages: (1) the development of a draft of hospital ethics accreditation standards; and (2) conducting a nationwide hospital survey of the proposed standards. Results: This study produced a tentative draft of hospital ethics accreditation standards comprised of six chapters and 62 standards based on the expert focus group and Delphi technique. The six chapters are: Medical ethics policies, regulations and leadership; The establishment and operation of a medical ethics committee; The establishment and operation of research-related ethics committees; Medical ethics education; Organisational ethical climate; and Respect for patients' rights and establishment of good hospital-patient relationships. The hospital survey indicated that the concept of an organisational ethical climate was new to most hospital managers, most hospitals disliked the idea of having a separate hospital ethics accreditation system, and small hospitals were concerned about their ability to comply with all of the standards. Conclusions: Regardless of whether hospital ethics accreditation can be a stand-alone accreditation or just part of existing hospital accreditation programmes, we hope this draft can serve as a good reference for future endeavours by hospital accreditation authorities.